PEMBENTUKAN DAN PELATIHAN KADEK SAJIKU (SEHAT JIWAKU) SEBAGAI UPAYA MEWUJUDUKAN DESA SIAGA SIEHAT JIWA MASYARAKAT TELUK TOMINI - M Soeli, Yuniar; dr. M. Yusril Ihza Djakaria; Nirwanto K. Rahim (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
The Mental Health Alert Village (DSSJ) is a community-based mental health program service model formed from the alert village's development. A form of community empowerment through a community-based mental health service approach, namely the formation and training of mental health cadres. Cadres play a role in identifying risk groups through data collection, early detection, providing health education, motivating patients and families and conducting program outreach to the community. This Thematic KKN service aims to empower the community by forming and training serving (healthy my soul) cadres. The methods include training, lectures, questions and answers, discussions and practice. This program is in collaboration with the Tabongo Village Government, Dulupi. Implementation of activities at the preparation stage emphasizes the preparation of teams and partners through joint coordination meetings regarding the need for implementing actions. This activity was part of my mental health care training (SAJIKU). Community participation in training for enthusiastic cadres was targeted at 80% of those invited to attend; in reality, 100% followed. There was an increase ine-ISSN : 2715-9558 p-ISSN : 2716-0912 Volume 6 Issue 153Jurnal Pengabdian Kepada Masyarakat Ungu (ABDI KE UNGU)knowledge from pre and post-scores; the average pre-test score was 50 to 82 for the average post-test score. Cadres are expected to continue to practice learning about mental health by continuing to carry out mental health care activities and providing education to the community.